Decrease of tyrosine-O-sulfate-containing proteins found in rat fibroblasts infected with Rous sarcoma virus or Fujinami sarcoma virus. - Liu, M C (1984)
Our interest was aroused by the recent report by Huttner [ Huttner , W. B. (1982) Nature (London) 299, 273-276] on general sulfation of tyrosine residues of proteins in normal and malignantly transformed tissues. Here we report on the reduction of sulfation in embryonic rat fibroblasts, line 3Y1, infected with Rous sarcoma virus or Fujinami sarcoma virus. In view of the instability of tyrosine O-sulfate in strong acid, the protein sulfation was tested for after incubation with [35S]sulfate and exhaustive Pronase hydrolysis. We found in general a reduction of sulfation in transformed tissue. It was greatest in the fibroblasts permanently transformed with Rous sarcoma virus. When fibroblasts transformed by the temperature-sensitive Fujinami sarcoma virus, line ts225 -3Y1, were used for comparison of sulfation at nonpermissive and permissive temperatures, the latter showed a strong reduction. Furthermore, we tested these cells for the uptake of inorganic [35S]sulfate. Uptake appeared highly reduced in the permanently infected fibroblasts, but ts225 -3Y1 grown at permissive and nonpermissive temperatures exhibited no difference. Uptake at both temperatures was comparable to uptake by normal 3Y1 cells. A recently much investigated cell surface protein, fibronectin, was reported to be lost on malignant transformation and to contain sulfate in an undetermined location. We found that ts225 -3Y1 cells grown at permissive temperature released fibronectin that contained tyrosine O-sulfate.